An Affair to remember - Wald, Jerry 1911-1962; McCarey, Leo; Daves, Delmer 1904-1977; Grant, Cary 1904-1986; Kerr, Deborah 1921- (Twentieth Century-Fox Film Corp., 1993)
A handsome bachelor and a cabaret singer meet on a luxury liner bound for New York. Although both are involved with other people, they fall in love. When the ship docks they agree to spend six months apart as a test of their love. But a tragic accident keeps them from their rendezvous and leaves their future uncertain.